LIFESTYLE AND FASHION AS COMMUNICATION (Semiotics of Lifestyle and Fashion as Shown for Self-Identity Yogyakarta Teenagers) - Retno Hendariningrum; Agung Prabowo (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
Fashion and lifestyle had already become part an integral from teenager life society today. Both—no longer essence, however, like packaging. Economy globalization and media industry globalization allegedly is the factor which format that condition. Capitalism is not only succeed embracing young teenage girl, but also the boy. This research aims for reveal the meaning of lifestyle and fashion in Yogyakarta teenager. This research use qualitative method. This research categorized into interpretive social research. Interpretive perspective associated with hermeneutics, that is—a theory about meaning. In method using semiology of communications analysis. Semiology used for pointed or saying the science of signs. Resource data obtained from observation, interview, and literature. The result of research pointed that the first, self-actualization is the first requirement of human. This is seen, when eating in the best restaurant isn’t survival, but consumed it for self-actualization is the part of urban middle-class bourgeois empire. Second, meaning of objects is not used as it should, but images of the bourgeoisie who surrounded the stuff. Third, our lifestyle is no longer decisive. Ranging from how to think, how to eat, how to dress, how to behave. Economic globalization and the globalization of media industries are factors that format the condition